2007
DOI: 10.1037/0894-4105.21.6.778
|View full text |Cite
|
Sign up to set email alerts
|

Response inhibition deficit is involved in poor decision making under risk in nonamnesic individuals with alcoholism.

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 50 publications
11
116
2
6
Order By: Relevance
“…In agreement with this viewpoint, recent studies reveal that ADHD children's dysfunction in inhibition control might have something to do with their decision-making deficit (see Geurts, van der Oord, & Crone, 2006). Similar results have been founded in individuals with alcoholism (Noel, Bechara, Dan, Hanak, & Verbanck, 2007). Patients with lesions in the ventral lateral prefrontal cortex (VLPFC), a region that is linked with uncertain or risky decision making (Goel & Dolan, 2000;McClure, Laibson, Loewenstein, & Cohen, 2004), also show difficulties on behavioral inhibition measures (Aron, Fletcher, Bullmore, Sahakian, & Robbins, 2003), implying the potential relationship between the inhibition function and the ability of making decisions (see also Sakagami et al, 2006).…”
Section: Influence Of Anxiety On Inhibition Function: Decision Makingsupporting
confidence: 71%
“…In agreement with this viewpoint, recent studies reveal that ADHD children's dysfunction in inhibition control might have something to do with their decision-making deficit (see Geurts, van der Oord, & Crone, 2006). Similar results have been founded in individuals with alcoholism (Noel, Bechara, Dan, Hanak, & Verbanck, 2007). Patients with lesions in the ventral lateral prefrontal cortex (VLPFC), a region that is linked with uncertain or risky decision making (Goel & Dolan, 2000;McClure, Laibson, Loewenstein, & Cohen, 2004), also show difficulties on behavioral inhibition measures (Aron, Fletcher, Bullmore, Sahakian, & Robbins, 2003), implying the potential relationship between the inhibition function and the ability of making decisions (see also Sakagami et al, 2006).…”
Section: Influence Of Anxiety On Inhibition Function: Decision Makingsupporting
confidence: 71%
“…Outro aspeto importante é a identificação de processos diferentes entre os primeiros e últimos ensaios da tarefa (Bechara, 2004;Brand, Labudda, & Markowitsch, 2006;Noel, Bechara, Dan, Hanak, & Verbanck, 2007), nomeadamente entre:…”
Section: Avaliação De Desempenho No Igtunclassified
“…Decorre, de acordo com os autores (Noel et al, 2007), uma mudança gradual na natureza da tarefa, ou seja, de tomada de decisão sob ambiguidade para tomada de decisão sob risco, sendo importante avaliar qual se encontra, ou não, deteriorada.…”
Section: Avaliação De Desempenho No Igtunclassified
“…Decision-making impairments in the IGT have been found in both substance abusers [39] and pathological gamblers [40]. From this perspective, Sun et al, [41] think that a myopia regarding future negative consequences could explain why persons suffering from PIU pursue their use of the Internet (e.g., excessive online gaming, compulsive consumption of pornographic material, online gambling) even if such behaviors will probably have tangible negative consequences for their daily lives.…”
Section: Problematic Internet Use and Controlled Aspects Of Self-regumentioning
confidence: 99%
“…Indeed, several studies have shown deficits in inhibitory control in other types of addictions such as substance use disorder [39] and pathological gambling [40]. In this vein, Cao et al, [32] and Sun et al, [41] have compared the performance of Internet addicts (based on the diagnostic criteria proposed by Young) and control participants on prepotent response inhibition.…”
Section: Problematic Internet Use and Controlled Aspects Of Self-regumentioning
confidence: 99%